Flipped Active Learning with Padlet: Developing Engagement and Metacognitive Skills - Roozafzai, Zahra Sadat (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study examines the impact of integrating Padlet, a web-based collaborative tool, into flipped learning environments to enhance active engagement and metacognitive development among students. A mixed-methods design was employed, combining pre- and post-course surveys, focus group discussions, and classroom observations. Participants included 50 undergraduate students enrolled in an Educational Science course, where Padlet was used for in-class activities in a flipped classroom setting. Quantitative data were collected using adapted scales (NSSE for engagement, SRQ for motivation, MAI for metacognitive skills) and academic performance metrics. Qualitative data were gathered through semi-structured focus groups and structured classroom observations. Descriptive statistics, paired t-tests, and thematic analysis were used for data analysis. Results indicated significant improvements in engagement (mean increase from 3.6 to 4.1, p = 0.02), motivation (3.8 to 4.3, p = 0.01), and metacognitive skills (3.4 to 3.9, p = 0.04). Qualitative findings highlighted enhanced collaboration, self-regulation, and critical thinking. The study concludes that Padlet-enhanced flipped classrooms effectively support active learning and metacognition, recommending its integration for student-centered instructional design.